Molecular markers and genome mapping in cowpea - Fatokun, C.A.; Young, N.; Myers, G. (1997)
Molecular markers such as RFLPs exist in almost limitless number in all organisms, and these could be very useful in monitoring the loci of genes that control important traits, as well as in studying genome evolution and structure. In cowpea, a genome map based mainly on RFLP markers has been developed. This map presently has 92 markers and spans 717cm of the genome. Using this map, quantitative trait loci (QTLs) for seed weight, pod length, and aphid resistance have been identified. Phylogenetic relationship among 44 genotypes belonging to different varieties, species, and sections in the genus Yigna was ascertained, following RFLP analysis. A comparison between the genomes of cowpea (Vigiia wiguiciilata) and mung bean (V. radiata) showed that nucleotide sequences were generally conserved but entire linkage groups were nol. although several large linkage blocks were still maintained by both crops.